Gleeble® simulation of the heat-affected zones in lean duplex stainless steel 2404: Understanding the effect of cooling rates on microstructure evolution and pitting corrosion resistance - C.L. Kugelmeier; R. Silva; A.A. Mendes Filho; R. Magnabosco; A.M. Kliauga; C.A.D. Rovere (Journal of Materials Research and Technology)
Physical simulations of single-pass welding on lean duplex stainless steel (LDSS) 2404 were performed to obtain heat-affected zones (HAZs) at different cooling rates (200–1 °C/s) to evaluate the effects on microstructure changes and corrosion resistance. The findings showed that fast cooling rates resulted in insufficient austenite formation. The austenite mainly consisted of grain boundary austenite (GBA), Widmanstätten austenite (WA), and intragranular austenite (IGA). For the highest cooling rate, there was a remarkable precipitation of high-temperature Cr nitrides (Cr2N) and a high degree of sensitization (14.90%), significantly impairing the corrosion resistance. The influence of these Cr2N on LDSS 2404 was shown to be influenced by their amount, distribution, the region where precipitation occurred (α/α boundaries and α/γ interfaces), and the cooling rates applied.